The economic impact of the demographic crisis its implications on public policy - Medalla, Felipe M. (The Philippine Review of Economics, 2004)
The Philippines is "over-populated" not in relation to its natural carrying capacity but in relation to the performance of its economy and government. Clearly, it would be better to improve the performance of the government and the economy than to just get government involved in fertility choices of households. However, given the history of the performance of both government and the economy, population policy can clearly help improve the nation's welfare. Government must provide public goods and services, but its capability to deliver them is affected by population growth. Moreover, the impact of high fertility on government may be even more serious than suggested by the average level of total fertility rate since children's education is closely correlated with their parents' education, and poorer and less educated parents tend to have more children. Government's ability to meet the needs of the population will clearly be improved if fertility can be brought down. Fertility can be reduced significantly without resorting to coercive policies. Poor and less educated parents have higher fertility than average, but their desired fertility is much lower than their actual fertility. Population policy can go a long way simply by helping people attain their desired family sizes.